Therapeutic Drug Monitoring of Voriconazole in Children with Hematologic Malignancy and Invasive Fungal Infections: An RCT from a Tertiary Care Centre in India - Sharad, Neha; Singh, Gagandeep; Xess, Immaculata; Agarwal, Reshu; Seth, Tulika; Reeta, K.H.; Kothari, Sweta (Cardiovascular & Haematological Disorders - Drug Targets, 2023)
Introduction: Voriconazole is a triazole anti-fungal with non-linear kinetics and a narrow therapeutic range. The objective of our study was to monitor the voriconazole serum levels in children with hematological malignancy and clinically suspected invasive fungal infections.Methods: The study was a prospective, randomized controlled trial conducted from June 2016 to December 2017. All children who had haematologic malignancies with clinically suspected invasive fungal infections and received voriconazole as the only anti-fungal were included in the study. The children were randomly allotted into two groups; one was the group that underwent TDM, and the other, TDM, was not done. Bioassay was the method employed for TDM. The trough levels were evaluated on a sample obtained on the fifth day of starting the drug. The institute's ethics committee approved the study.Result: A total of 30 children were included in the study: 15 in the TDM group and 15 in the non-TDM group. The most common underlying malignancy was AML. Neutropenia due to chemotherapy sessions was these patients' most common risk factor. A favorable outcome was seen in 13/15 (86.7%) in the TDM group and 11/15 in the non-TDM group (73.3%).Conclusion: Only five out of 15 (33.3%) children had voriconazole serum levels within the therapeutic range. Alterations in dose had to be done in the remaining to achieve the recommended serum levels. Thus, we recommend TDM for all children of hematologic malignancy receiving voriconazole for better management. Our findings also revealed that children with AML had lower than recommended levels of voriconazole on TDM evaluation, whereas those with ALL had normal to elevated levels of voriconazole.
Keywords: Voriconazole